Personalized checkpoint acupuncture can reduce postoperative pain after abdominal surgery - a STRICTA-conform pilot study - Ghanad, Erfan; Yang, Cui; Weiß, Christel; Goncalves, Mario; Santos, Maria Joao; Correia, Nuno; Reißfelder, Christoph; Greten, Henry Johannes; Herrle, Florian (Langenbeck's archives of surgery, 2023)
Background: Optimal pain management is one of the core elements of Enhanced Recovery After Surgery (ERAS®) protocols and remains a challenge. Acupuncture (AC) is an effective treatment for various pain conditions. Systematic and personalized allocation of acupoints may be decisive for efficacy. Methods: Based on the predominant pressure sensitivity of six gastrointestinal (GI) checkpoints (G1-G6), we devised a method to detect personalized patterns of pain and a corresponding set of acupoints. We performed a single AC treatment with semi-permanent needles and assessed the visual analogue scale (VAS) score, pain threshold based on pressure algometry (PA), and temperature changes on abdominal skin areas before and 5 min after AC. Results: Between April and June 2021, thirty-eight patients were prospectively included in this pilot study. The mean reduction in subjective pain sensation as assessed by VAS was 86%, paralleled by an augmentation of the pain threshold as measured by PA by 64%. A small but significant increase in the skin temperature was observed above the abdominal surface. These effects were independent of the type of surgery. Conclusion: Checkpoint acupuncture may be a complementary tool for postoperative pain management. Further investigations are needed to explore this analgesic effect.
Online veröffentlicht: 10. Oktober 2023
Gesehen am 20.12.2023